2013
DOI: 10.3758/s13414-013-0503-4
|View full text |Cite
|
Sign up to set email alerts
|

More than just perception–action recalibration: Walking through a virtual environment causes rescaling of perceived space

Abstract: Egocentric distances in virtual environments are commonly underperceived by up to 50 % of the intended distance. However, a brief period of interaction in which participants walk through the virtual environment while receiving visual feedback can dramatically improve distance judgments. Two experiments were designed to explore whether the increase in postinteraction distance judgments is due to perception-action recalibration or the rescaling of perceived space. Perception-action recalibration as a result of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
87
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(95 citation statements)
references
References 52 publications
7
87
1
Order By: Relevance
“…Although the direct relationship between perceived size and distance has been questioned, judged distance and size have been shown to be highly correlated (Gogel, Loomis, Newman, & Sharkey, 1985;Hutchison & Loomis, 2006), presumably due to the impact of perceived distance on both perceptual variables (Brenner & van Damme). Kelly et al (2013) found that object size judgments increased after a walking interaction, consistent with an increase in perceived distance. More recently, Kunz, Creem-Regehr, and Thompson (2015) tested the effects of visual feedback, indicating faster-or slower-than-actual walking speed in a VE.…”
supporting
confidence: 48%
See 2 more Smart Citations
“…Although the direct relationship between perceived size and distance has been questioned, judged distance and size have been shown to be highly correlated (Gogel, Loomis, Newman, & Sharkey, 1985;Hutchison & Loomis, 2006), presumably due to the impact of perceived distance on both perceptual variables (Brenner & van Damme). Kelly et al (2013) found that object size judgments increased after a walking interaction, consistent with an increase in perceived distance. More recently, Kunz, Creem-Regehr, and Thompson (2015) tested the effects of visual feedback, indicating faster-or slower-than-actual walking speed in a VE.…”
supporting
confidence: 48%
“…One common approach to improving distance perception in VR allows participants to interact with the VE while receiving visual feedback (Kelly, Donaldson, Sjolund & Freiberg, 2013;Kelly, Hammel, Siegel, & Sjolund, 2014;Mohler, Creem-Regehr & Thompson, 2006;Richardson & Waller, 2005, 2007Waller & Richardson, 2008). In a prototypical study by Waller and Richardson (2008), participants performed preinteraction distance judgments, followed by interaction and then postinteraction distance judgments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic events also do not help subjects to improve their distance judgment. Subjects in a virtual environment performing a walk task showed that the perception of walked distances were not correlated with their previously distance judged [24]. These authors also found an underestimation of distance to egocentric judgment, a result that is in line with ours.…”
Section: Figuressupporting
confidence: 81%
“…The current project compared the relationship between frontal and depth extents in two VEs: the indoor classroom environment used by Geuss et al (2012) and a barren outdoor environment consisting of a ground plane covered in a grass texture, which has produced relatively large underperception of egocentric distance in our laboratory (Kelly, Hammel, Siegel, & Sjolund, 2014). Similar outdoor VEs have been used in numerous experiments testing distance perception (Kelly, Donaldson, Sjolund, & Freiberg, 2013;Li et al, 2013;Messing & Durgin, 2005;Richardson & Waller, 2005;Waller & Richardson, 2008;Wu, He & Ooi, 2007;Ziemer, Plumert, Cremer & Kearney, 2009). We expected that manipulation of the VE (room vs. grass) would affect judgments of depth extents, with smaller judgments in the grass VE compared to the room VE.…”
mentioning
confidence: 99%